Determination of new generation amide insecticide residues in complex matrix agricultural food by ultrahigh performance liquid chromatography tandem mass spectrometry - Tao Lin (Nature Portfolio, 2021)
Abstract Eight new generation amide insecticide residues analysis by multiwalled carbon nanotubes (MWCNs) cleanup, combined with QuEChERS and ultrahigh performance liquid chromatography tandem mass spectrometry has been developed and successfully applied in complex matrix such as orange, celery, onion, litchi, mango, shallot, chives, avocado, garlic. The matric effect of MWCNs is optimized and compared with ordinary cleanup materials. The results show that the performance of MWCNs is fine and effectively reduce matrix interference. Through chemical structure skeletons analyzed, chlorantraniliprole, bromoantraniliprole, and cyantraniliprole can cause same product ions of m/z 286.0 or 177.1 in the ESI+ mode, then tetrachlorantraniliprole and cyclaniliprole can produce collective ions of m/z 146.9 in the ESI− mode. The coefficients (R 2) were greater than 0.9990, the limit of quantification ranges from 0.03 to 0.80 μg/kg, the recovery rate ranges from 71.2 to 120%, and the relative standard deviation (RSD) ranges from 3.8 to 9.4%. The method is fast, simple, sensitive, and suitable for the rapid determination of amide pesticides in complex matrix agricultural food.